Phytochemical and Larvicidal Activity of Pineapple (Annanas comusus L.) Peel Extract Against Aedes aegypti of Dengue Vector (Journal of Pharmaceutical Negative Results, 2021)
Control of the Aedes aegypti DHF vector with synthetic insecticides has an impact on resistance. As an alternative is the use of plant materials, one of which is pineapple skin waste which is widely available and has not been utilized. This study aims to determine the phytochemical compounds contained and biolarvicidal activity of pineapple peel against Aedes aegypti. Held. Laboratory experimental study with randomized block design effect of concentration on mortality of Aedes aegypti larvae Based on the research results, the ethanol extract of pineapple peel contains flavonoids, tannins, saponins, alkaloids and terpenoids and these compounds have biolarvicidal activity. Ethanol extract at concentrations of 400 ppm and 500 ppm and at concentrations of 100 to 300 ppm has very low activity. Letal Konsentrasi ektrak ethanol kulit nanas adalah Pineapple peel ethanol extract has potential in the future as an environmentally friendly biolarvicidal.